Dona Barbara, from an Amazon Ogress to a Loving Mother: A Tale of Revenge and Love - Adhikari, Bam Dev (Literary Studies, 2020)
Venezuelan novelist Romulo Gallegos’ novel Dona Barbara (1929) is set in Venezuelan llanos and it depicts the conflict between barbarism and civilization that is represented by the figure of an amazon ogress and the figure of a good mother of the same woman named Dona Barbara. The specific setting of the novel, the Altamira ranch is a huge estate in the wildest section of the Arauca River basin of Venezuela, a ranch that was established early in the history of the country’s cattle business. Altamira gets neglected by its owner for years until Santos Luzardo, the successor of the ranch, a lawyer and a Ph. D. from the University of Carcass arrives there and tries to set the anarchy in order. On the other hand, the Altamira ranch borders the El Miedo ranch, owned by a ruthless woman, an amazon named Dona Barbara, who becomes the owner of the ranch by the use of tricks and treachery. Dona Barbara tries to expand her ranch by trespassing the neighboring ranches with the forces of witchcraft, superstition and deceit. As Skurski calls her, “a personification of rural despotism” (617), she rules the llanos for pelf and power with revenge from men as her central motive. Brian Gollnick comments on this conflict as “Santos Luzardo triumphing through a plan to rationalize territorial organization and agriculture under an enlightened authority which contrasts to Dona Barbara’s black magic and despotic charisma” (450). Thus, the novel establishes two lines, in the beginning, the line of civilization represented by Santos Luzardo and the line of barbarism represented by Dona Barbara. The novelist has associated the line of barbarism with the ogress figure and civilization with the mother figure of the same woman, Dona Barbara.